A population balance cavitation model. (May 2021) - Li, Jiajia; Carrica, Pablo M.
Highlights: Effects of ship motions on the airwake are studied for two wave conditions. One- and two-way coupled approaches used to analyze effects on a helicopter. Motions corresponding to sea state 6 waves have considerable effects on airwake and helicopter. Fluctuations due waves and motions cannot be added linearly to no-motions fluctuations. Large craft cause considerable induced air flow, requiring two-way coupled analyses. Abstract: We propose a novel polydisperse cavitation model based on population balances, which seeks to provide the bubble size distribution in addition to the void fraction, enabling natural prediction of transitions from large bubbles to small cavities in regions of massive condensation, or from small bubble to large cavities in regions of strong evaporation. The mass transfer rate is modeled from the asymptotic solution of the Rayleigh-Plesset equation with modifications for the polydisperse approach. Existing breakup and coalescence models, which do not include effects of mass change, are adapted and new models are developed to account for evaporation and condensation. In addition, homogenous and heterogeneous nucleation models are incorporated to treat the activation and size distribution of nuclei. The model is evaluated against data for the Delft twisted foil, showing satisfactory results for the pressure distribution, forces, and shedding frequency. Though no experimental data for the bubble size distribution is available, bubble sizes in different regions of the flow predicted by the model indicate the right trends observed in videos and photographs of the experiments. Refinements to the model based on experiments are necessary, especially to evaluate the ability to properly predict void fraction and bubble size distribution.